Surgical Management of Fuchs Endothelial Corneal Dystrophy: A Treatment Algorithm and Individual Patient Meta-Analysis of Descemet Stripping Only. Issue 9 (25th September 2022) - Din, Nizar; Cohen, Eyal; Popovic, Marko; Mimouni, Michael; Trinh, Tanya; Gouvea, Larissa; Alshaker, Sara; Ong Tone, Stephan; Chan, Clara C.; Slomovic, Allan R.
Abstract : Purpose: This study aims to determine predictive factors for success of Descemet stripping only (DSO) in Fuchs corneal endothelial dystrophy and propose a DSO treatment algorithm. Methods: Ovid MEDLINE, Embase, and Cochrane CENTRAL databases were searched to evaluate DSO case series, including combined phacoemulsification and DSO, and the use of Rho-kinase inhibitors (ROC-i). Our primary outcome was success of corneal clearance. Secondary outcomes included the time to corneal clearance, the postoperative endothelial cell count (ECC), and the impact of ROC-i. Results: Sixty-eight cases were evaluated with a mean follow-up of 12.4 months. DSO corneal clearance was achieved in 85% (n = 58) with a mean time of 4.9 weeks for the ROC-i group compared with 10.1 weeks in the observation group ( P < 0.0001). The mean central ECC postoperatively was higher in the ROC-i group compared with the observation group 1151 ± 245 versus 765 ± 169 cells/mm 2, respectively ( P < 0.018). The postoperative best-corrected visual acuity (BCVA) improved in 61 eyes (90%), with mean final BCVA of 0.17 (0.26) logMAR ( P = 0.001), which was statistically significant compared with preoperative BCVA. Factors influencing success were 4-mm descemetorhexis size, a clear peripheral ECC with no clinical sequelae of decompensation or guttae, and a low central corneal thickness. No intraoperative complications were noted. The commonest postoperative complication was deep corneal stromal scars noted at the descemetorhexis edge (n = 9). Conclusions: DSO has a role in the treatment of a subset of patients with Fuchs corneal endothelial dystrophy and that adjuvant treatment with ROC-i may lead to faster corneal clearance.